The Challenge of The Bawaslu In Supervision Politics of Power Nepotism in Nagan Raya, Aceh - Muklir; Ferizaldi (Jurnal Transparansi Publik (JTP), 2025)
Challenges Supervising the election of regional heads which are followed by candidates from families of incumbents or former officials. Usually there is money politics, budget politics, or the mobilization of the state civil apparatus. To overcome these challenges, Bawaslu cooperates with monitoring institutions, including law enforcement agencies such as the Corruption Eradication Commission to anticipate violations in areas where political dynasties are growing. The core problem of this research is about Ampon Bang as Regent of Nagan Raya Regency and his wife as Chair of the People's Representative Council of Nagan Raya Regency and his family and cronies occupy strategic positions in his government. The type of research used is qualitative, primary and secondary data sources, data collection methods used are observation, interviews and documentation. In analyzing the problem applying data reduction, data verification and conclusion drawing. The theory used in this research is the theory of power, the theory of kinship systems and the theory of political capital. The results showed that the establishment of the Political Nepotism of Power of Ampon Bang Using the concept of family and cronies with a political strategy that was carried out by placing family and relatives in the organizational structure of the government and closing the space for public participation by carrying out political doctrines for civil servants and village apparatus. This doctrine is carried out in an effort to win the family and relatives who take part in the contestation.